Assessment of Drug Use Pattern Using WHO Core Drug Use Indicators in Two Primary Health Care Centers of Sunsari District, Eastern Nepal (Purbanchal University Health Journal, 2022)
Introduction: Rational use of drugs is the matter of global concern in today’s world. Drug utilization studies are an important tool to evaluate drug utilization practices.Objective: The objective of this study was to assess drug use patterns in two Primary Health Care Centers (PHCCs), namely Chatara and Itahari PHCC, of Sunsari district using standard WHO core drug use indicators.Method: A cross-sectional descriptive study was conducted using WHO core drug indicators. Descriptive statistics were used for data analysis.Result: A total of 609 prescriptions were analyzed. The average number of drugs prescribed was 2.64 (±1.03). Percentage of encounters with at least one antibiotic prescribed was 70.77% whereas encounters with at least one injection prescribed was low 0.66%. The total percentage of drugs prescribed using generic names was found to be 59.93% and the percentage of drugs prescribed from EDL was 68.51%. The average consultation and dispensing time was 6.60 minutes and 99.45 seconds respectively. Only 17.73% of patients had adequate knowledge of the drug whereas none of the drugs were adequately labelled. Percentage of drugs actually dispensed was 64.22%. The total percentage of availability of key drugs in health facilities was 90.63%. The most common morbidity was respiratory tract infections i.e. 129 (21.18%), acid peptic disease (APD) 77 (12.64%), allergies 64 (10.51%) and dental caries 62 (10.18%). A total of 1607 drugs were prescribed in 609 prescriptions. The most commonly prescribed drug class was antimicrobials 449(27.95%) followed by antipyretics 260 (16. 18%).Conclusion: Among the prescription evaluated, the rational prescribing and dispensing practice was inadequate mainly reflected by high antibiotics encounters, low generic prescribing, inadequate labeling and poor patient’s knowledge of drugs. Effective intervention programs are encouraged in these health facilities for the prescribers and the dispensing health personnel for promoting rational use of medicines.